2016
DOI: 10.1111/bpa.12350
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Skeletal Muscle in Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal adult-onset disease primarily characterized by upper and lower motor neuron degeneration, muscle wasting and paralysis. It is increasingly accepted that the pathological process leading to ALS is the result of multiple disease mechanisms that operate within motor neurons and other cell types both inside and outside the central nervous system. The implication of skeletal muscle has been the subject of a number of studies conducted on patients and related animal mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
120
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(135 citation statements)
references
References 135 publications
(62 reference statements)
3
120
0
Order By: Relevance
“…Masitinib treatment also prevented the regressive remodeling of perisynaptic Schwann cells described in ALS (67,68). Because Schwann cell dissociation from NMJ is mainly caused by the axon retraction from motor plates (17,68), our results further suggest the halt of distal motor axon degeneration following treatment with masitinib.…”
Section: Discussionsupporting
confidence: 62%
“…Masitinib treatment also prevented the regressive remodeling of perisynaptic Schwann cells described in ALS (67,68). Because Schwann cell dissociation from NMJ is mainly caused by the axon retraction from motor plates (17,68), our results further suggest the halt of distal motor axon degeneration following treatment with masitinib.…”
Section: Discussionsupporting
confidence: 62%
“…In the present study, edaravone treatment significantly reduced the oxidative stress serum markers dROM and the OS index, and Nrf2 expression in spinal motor neurons and LL myofibers (Figures d,e, , , ). It also reduced the expressions of PGC1α and HDAC4 in myofibers (Figure ), suggesting edaravone treatment enhanced mitochondrial function and muscle development (Loeffler et al, ; Petri et al, ; Thau et al, ). Furthermore, edaravone treatment ameliorated neurogenic myofiber atrophy, spinal motor neuron loss, astrogliosis and motor performance impairment measured by the rotarod test in Nrf2/G93A mice (Figures c, , ).…”
Section: Discussionmentioning
confidence: 92%
“…ALS skeletal muscles are involved in oxidative stress, mitochondrial dysfunction and bioenergetic disturbances (Loeffler et al, ; Tsitkanou et al, ). In the present study, Nrf2/G93A mice showed neurogenic myofiber atrophy, denervated NMJ and Nrf2 expression of small quadriceps myofibers in LL, which were significantly alleviated by edaravone, except for the NMJ denervation (Figures ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One limit is the availability of CSF and the consequent challenge of finding adequate controls. The main advantage of blood samples is the ability of collection during longitudinal studies; thus, it is Some studies have advocated that muscle per se may be impaired by the pathogenesis of the disease, principally through the "dying-back" phenomenon [17] [18]. Muscle has been poorly studied, and its central role in energetic metabolism suggests that this tissue warrants further analysis in order to find biomarkers and to compare muscular metabolism with those of the brain and the body overall [19].…”
Section: Sources Of Biomarkersmentioning
confidence: 99%